2016
DOI: 10.1155/2016/4976150
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumor of the Bladder: 2 Rare Cases Managed with Laparoscopic Partial Cystectomy

Abstract: Two cases of inflammatory myofibroblastic tumor (IMT) of the bladder are reported here. Both patients were male and presented with macroscopic hematuria; in the first case terminal hematuria was associated with irritative voiding symptoms. The second case was a smoker with hematuria unresponsive to medical treatment and anemia. Clinical presentation, pathological features, treatment, and prognosis are discussed. Due to rarity of this pathological condition, there are no guidelines concerning treatment and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…There are no standardized schemes regarding follow-up, but it is advisable since this tumour has 25% recurrence. However, given the indeterminate biological behavior of these tumours, continued monitoring of their clinical course is strongly recommended [11] .…”
Section: Discussionmentioning
confidence: 99%
“…There are no standardized schemes regarding follow-up, but it is advisable since this tumour has 25% recurrence. However, given the indeterminate biological behavior of these tumours, continued monitoring of their clinical course is strongly recommended [11] .…”
Section: Discussionmentioning
confidence: 99%
“…We compared the results of published case reports to collate the existing evidence derived from retrospective cohorts and case series. [ 24 25 26 27 28 29 30 31 32 ] Despite that, the literature remains scarce regarding the optimal diagnosis, management, and follow-up protocol for IMTs of the bladder. The largest systematic review on the topic included 182 patients, but included both the IMTs and pseudosarcomatous myofibroblastic proliferation of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies and case series,[ 24 25 26 27 28 29 30 31 32 ] the age of the patients diagnosed with bladder IMTs ranged between 3 and 89 years (mean age of 44 years), and the most common clinical presentation was gross hematuria, in more than 60% of the cases. While the pathological type was variable, the most common type of bladder IMT was the spindle cell pattern [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 Sofia et al have reported 2 cases treated with laparoscopic partial cystectomy to achieve total resection, and no recurrence was noted after 58 months of follow-up. 6 However, there are no studies regarding a safety margin during partial cystectomy in cases of IMTs, and although it is required to achieve free resection margins, the benefit of negative margin resection must be weighed against the bladder capacity and function preservation in patients whose tumor invades only superficial layer and are of relatively old age. Teoh et al's have conducted a systemic review, and among the 182 patients, 60.8% were treated with TURBT and they indicated that most cases can be adequately treated with transurethral resection.…”
Section: Discussionmentioning
confidence: 99%
“…In the consideration of complete local resection, the treatment option includes TURBT and partial cystectomy. Concerning the possibility of local recurrence, partial cystectomy is often the treatment option to ensure total resection of the tumor 2,6,7 . Sofia et al have reported 2 cases treated with laparoscopic partial cystectomy to achieve total resection, and no recurrence was noted after 58 months of follow‐up 6 …”
Section: Discussionmentioning
confidence: 99%